Patient Education Regarding Fasting Recommendations to Shorten Fasting Times in Patients Undergoing Esophagogastroduodenoscopy: A Controlled Pilot Study. (20th September 2022) - van Noort, Harm H. J.; Lamers, Carlijn R.; Vermeulen, Hester; Huisman-de Waal, Getty; Witteman, Ben J. M.
Abstract : This study evaluated the applicability and efficacy of patient education regarding fasting recommendations to shorten fasting times in patients undergoing esophagogastroduodenoscopy (EGD). A prospective nonrandomized controlled pilot study was performed. The intervention group (IG) was educated by nurses to eat until 6 hours and drink until 2 hours before EGD. The control group (CG) received usual care. Outcomes were applicability as perceived by patients, adherence to fasting recommendations, gastric visibility, and patients' comfort. A total of 109 patients were included of whom 42 were IG patients (37%). Patients' perspectives on fasting, their experienced discomfort, professional support, and circadian rhythm influenced application of fasting recommendations. Adherence to length of fasting from foods improved with 3:14 hours ( p < .001) and from liquids with 5:22 hours ( p < .001) in the IG compared with the CG. Gastric visibility during EGD was better in the IG than in the CG. The IG patients experienced significant less thirst, hunger, headache, and anxiety. To successfully reduce fasting times, fasting education should include positive, individual instructions, which help patients apply the fasting recommendations within their biorhythm. Positive, concrete instructions by nurses shortened fasting times before EGD, which improved gastric visibility and reduced patient discomfort.